Discharge coefficient of a triangular side-weir located on a curved channel - Cosar, A; Agaccioglu, H (ASCE-AMER SOC CIVIL ENGINEERS, 2004)
This study aims to obtain sharp crested triangular side-weirs discharge coefficients both in the straight channel and along the bend by using a total of 1,735 experiments. It was found that triangular side-weirs discharging coefficients along the bend depend on the upstream Fronde number in the main channel (F), the apex angle of side-weir (theta), and the bend angle (alpha). Because there is much greater intensity of secondary flow created by lateral flow with an increase of the overflow length, sharp crested triangular side-weirs discharge coefficients of the apex angle theta = 120degrees were achieved more frequently than the others even at the straight channel in subcritical flow conditions. In a curved channel, the path of maximum velocity and the secondary current created by the bend both cause a much greater deviation angle towards the side-weir which is involved within F and L/b. Therefore, triangular side-weirs discharging coefficients along the bend are greater than the values obtained in the straight channel.
Keywords: water discharge; discharge coefficients; intakes; hydraulic structures; weirs; channel flow; curvature; FLOW; Agriculture; Engineering; Water Resources